Assessing information needs tools, techniques, concepts for the Internet age - Nicholas, David (London Aslib, 2000)
A series of short practical guides on how to deal with, and resolve, issues of current interect or concern to those working or teaching in the field of library and information services.Prepared by practitioners who are experts in the field, the guides offer a 'how to' approach based on current goood practice which has been proved to work.-back cover
Includes bibliographical references (pages 155-160)
Keywords: Needs assessment; Information services